2016
DOI: 10.1161/hypertensionaha.115.06461
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stroke Risk Due to Partial White-Coat or Masked Hypertension Based on Home and Ambulatory Blood Pressure Measurements

Abstract: The prognostic significance of white-coat hypertension (WCHT) is controversial, and different findings on self-measured home measurements and 24-h ambulatory monitoring make identifying WCHT difficult. We examined whether individuals with partially or completely defined WCHT, as well as masked hypertension, as determined by different out-of-office blood pressure measurements, have a distinct long-term stroke risk. We followed 1464 participants (31.8% men; mean age, 60.6±10.8 years) in the general population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 41 publications
(43 reference statements)
2
56
1
5
Order By: Relevance
“…Studying Japanese adults in the Ohasama cohort, Satoh et al looked at the association of stroke with masked hypertension diagnosed on ABPM only (using daytime, 24-hour, and/or nighttime periods), HBPM only, or on both out-of-clinic BP measurement modalities. (49) They found that masked hypertension detected on both ABPM and HBPM was associated with an increased risk of stroke (HR 2.05, 95% CI 1.23 – 3.41) compared to sustained normotension defined as having non-elevated clinic BP, non-elevated BP on ABPM, and non-elevated BP on HBPM. Further, this risk was also elevated among individuals with masked hypertension diagnosed only on ABPM but not on HBPM (HR 1.93, 95% CI 1.15 – 3.24); and when diagnosed on HBPM but not ABPM (HR 2.26, 95% CI 1.32 – 3.89).…”
Section: Adverse Outcomesmentioning
confidence: 99%
“…Studying Japanese adults in the Ohasama cohort, Satoh et al looked at the association of stroke with masked hypertension diagnosed on ABPM only (using daytime, 24-hour, and/or nighttime periods), HBPM only, or on both out-of-clinic BP measurement modalities. (49) They found that masked hypertension detected on both ABPM and HBPM was associated with an increased risk of stroke (HR 2.05, 95% CI 1.23 – 3.41) compared to sustained normotension defined as having non-elevated clinic BP, non-elevated BP on ABPM, and non-elevated BP on HBPM. Further, this risk was also elevated among individuals with masked hypertension diagnosed only on ABPM but not on HBPM (HR 1.93, 95% CI 1.15 – 3.24); and when diagnosed on HBPM but not ABPM (HR 2.26, 95% CI 1.32 – 3.89).…”
Section: Adverse Outcomesmentioning
confidence: 99%
“…Ambulatory BP level had already many years ago been shown to be better predictor for cardiovascular complications as compared to clinic BP readings [24,25]. This was confirmed by prospective studies dealt with estimation of outcomes in patients with different BP phenotypesrisk of myocardial infarction, stroke, lethal outcomes and other cardiovascular complications was significantly higher in masked uncontrolled hypertension as compared to normotension and well controlled hypertension and was similar to cardiovascular risk in sustained hypertension [7,[26][27][28][29]. For instance, in accordance to Satoh M. et al data [29] (with mean follow-up of 17.1 years) the risk of stroke in masked un-АГТ -38,8% зимой и 27,8% летом.…”
Section: Discussionmentioning
confidence: 92%
“…Уже мно-го лет назад был доказан факт, что амбулаторное АД -луч-ший предиктор сердечно-сосудистых осложнений по сравнению с показателями клинических измерений [24,25]. Это подтверждают и проспективные исследования, по-священные оценке исходов при разных фенотипах АД, -риск инфаркта миокарда, мозгового инсульта, летальных исходов и других сердечно-сосудистых осложнений при скрытой АГ значимо выше, чем при нормотонии и эф-фективной АГТ, а также сопоставим с риском при устойчивой АГ [7,[26][27][28][29]. Например, в исследовании Satoh M. и соавт.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…9 According to the above, hypertensive patients in whom normal out-of-office BP required by both techniques, ABPM and HBPM, have an incidence of CV events similar to that of normotensive patients, while those with one of the two measures high and the other normal have an intermediate CV risk among normotensive and sustained hypertensive patients. 10,11 When these out-of-office measurements apply to the monitoring of treated hypertensive patients, it seems that both are useful and reliable. 12,13 When a patient has outof-office BP controlled according to any one of the measures, ABPM or HBPM, CV risk is independent of BP measurement in the office.…”
mentioning
confidence: 99%